-5+6(x-5)=12x+5-6x

Simple and best practice solution for -5+6(x-5)=12x+5-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+6(x-5)=12x+5-6x equation:



-5+6(x-5)=12x+5-6x
We move all terms to the left:
-5+6(x-5)-(12x+5-6x)=0
We add all the numbers together, and all the variables
6(x-5)-(6x+5)-5=0
We multiply parentheses
6x-(6x+5)-30-5=0
We get rid of parentheses
6x-6x-5-30-5=0
We add all the numbers together, and all the variables
-40!=0
There is no solution for this equation

See similar equations:

| a-5/5=12 | | 2/7x-5=1 | | 37x-15=180 | | 2k/7=11-k/2 | | 24/44=6/w | | 8/1.1=4.5/v | | -5(k-2)=-6(k-2) | | 3/6=(x+3)/8 | | 8s-(5s+6)=1/2(20+65) | | 9z^2+36z+36=0 | | (13^x)=47 | | 10m-5=15m-5 | | 5x-5=7x+30 | | 250((1+0.01)^x/0.01)=150,000 | | 8+5(x-3)=7-8(x-6) | | S+1e=-5 | | 3(2x+7)=6-5(2x-3) | | -12p+39=11p+154 | | −0.8n=4 | | (2y+5)=(4y-5) | | 155-3.50x=135-3x | | 4x+x-6x=10 | | 2x4−32x2=0 | | 2(r-3)-8=50 | | 4x=30-30(2) | | 4d-8=200-4d | | 14x+21=180 | | T-h(-15)=21 | | 8+4x=-10=x | | X+1-2-3+x=6-1+1 | | 1/x(50)-(25)=0 | | 4t^2-16+15=0 |

Equations solver categories